2010
DOI: 10.1111/j.1755-5922.2009.00132.x
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Yellow Wine and Red Wine Inhibit Matrix Metalloproteinase‐2 and Improve Atherosclerotic Plaque in LDL Receptor Knockout Mice

Abstract: Our previous study found that Chinese yellow wine could inhibit the production of homocysteine (HCY) induced extracellular matrix metalloproteinase‐2 (MMP‐2) in the cultured rat vascular smooth muscle cells. Little is known about the relationship between Chinese yellow wine and atherosclerosis or MMP‐2 in vivo. Thirty‐two LDL Receptor knockout mice on a high‐fat and l‐methionine diet developed plasma hyperhomocysteinemia and atherosclerosis. They were randomly divided into yellow wine group (n = 8), red wine g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 39 publications
1
15
0
1
Order By: Relevance
“…A total of 20 μg proteins of various treatments were mixed with sodium dodecyl sulfate (SDS) sample buffer without a reducing agent and loaded onto a 10% SDS-polyacrylamide gel (0.1 g/ml) containing 0.1% gelatin (1 g/L) as described previously (Guo et al, 2010). Clear zones against the blue background indicated the presence of gelatinase.…”
Section: Analysis Of Gelatinase Productionmentioning
confidence: 99%
“…A total of 20 μg proteins of various treatments were mixed with sodium dodecyl sulfate (SDS) sample buffer without a reducing agent and loaded onto a 10% SDS-polyacrylamide gel (0.1 g/ml) containing 0.1% gelatin (1 g/L) as described previously (Guo et al, 2010). Clear zones against the blue background indicated the presence of gelatinase.…”
Section: Analysis Of Gelatinase Productionmentioning
confidence: 99%
“…In the previous studies, we demonstrated the beneficial effect of rice wine on atherosclerosis in in vivo and in vitro experiments. 4,5 However, Chinese rice wine is a complex mixture containing various ingredients such as peptides, oligosaccharides, and polyphenols, and the exact ingredients that have the antiatherosclerosis effect are still unknown. 6 Increased homocysteine (Hcy) level in the blood has been demonstrated as an important risk factor for the development of cardiovascular diseases, and it has already been confirmed that Hcy could promote vascular smooth muscle cell (VSMC) migration and proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…Among these components, the polyphenols in huangjiu are related to many biological activities, including antioxidant activity, 19 anti- atherosclerotic activity 23,24 and the prevention of cardiovascular disease. 22 Solid phase extraction (SPE) is commonly used to extract polyphenols for further quantication and identication. However, this method has some disadvantages, as it is time-consuming and leads to a very low yield of polyphenols in huangjiu extraction (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…13 It has been implicated that polyphenolic compounds can be preventive and therapeutic agents for the treatment of various diseases due to their antioxidant properties. [19][20][21] In a previous study, 22 huangjiu showed great health benets for cardiovascular disease in mouse models with plasma hyperhomocysteinemia and atherosclerosis. Aer feeding with huangjiu, the plasma homocysteine (p < 0.01) and atherosclerosis lesion areas (p < 0.001) of the model mice were signicantly reduced compared to the control and ethanol groups.…”
Section: Introductionmentioning
confidence: 99%